Cele i koncepcje nauczania literatury (rys historyczny) = Thee aims and conceptions of teaching literature - a historical perspective - Świętosławska, Teresa (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The author presents the historical perspective of the aims and conceptions of teaching literature from the beginning of the 19th century to the outbreak of the Second World War.
Keywords: dydaktyka literatury; 19-20 w.